Living-Related Liver Retransplantation in a Child: When it Seems Impossible (A Clinical Case) - D. I. Novikov; A. Yu. Zaitsev; A. V. Filin; E. R. Charchyan; A. V. Metelin (Вестник анестезиологии и реаниматологии, 2022)
The objective: to show the possibility of anesthesia during liver retransplantation in a child in the absence of adequate vascular access.A clinical case of liver retransplantation in a 10-year-old patient with liver transplant dysfunction and acquired thrombophilia is considered. In 2011, the child underwent Kasai portoenterostomy, and in 2012, living-related transplantation of the left lateral liver bisegment from a related donor was performed due to liver cirrhosis as an outcome of biliary atresia. Also, the child had multiple surgical interventions due to perforations of the small intestine with underlying segmental venous mesenteric thrombosis. In the long term after the transplantation, irreversible transplant dysfunction developed with manifestations and worsening of hepatocellular insufficiency, encephalopathy, as well as recurrent bleeding from varicose veins of the esophagus and cardiac orifice. The clinical situation was complicated by the lack of adequate vascular access due to total thrombosis of the venous system, thrombosis of the superior and inferior vena cava. The only possible option for ensuring adequate venous access was the implantation of a tunneled catheter into the right atrium of the right atrium for prolonged standing in conditions of single-lung ventilation through right-sided thoracotomy.